2022
DOI: 10.1186/s10195-022-00673-4
|View full text |Cite
|
Sign up to set email alerts
|

VOLCON: a randomized controlled trial investigating complications and functional outcome of volar plating vs casting of unstable distal radius fractures in patients older than 65 years

Abstract: Background Primary aim: to compare complications of operative vs non-operative treatment of unstable distal radius fractures (DRF) fulfilling national clinical guidelines for operative treatment. Secondary aim: to compare the functional outcomes. Materials and methods A single-centre randomized controlled trial of unstable DRF. 50 patients: volar locking plate, 2 weeks casting + 3 weeks orthosis. 50 patients: 5 weeks casting. Primary outcome: compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…As to unstable DRFs, in an RCT by the Wrist and Radius Injury Surgical Trial (WRIST) Group, the authors found no clinically meaningful PRO difference 24 months after injury across VLPF, external fixation (EF), percutaneous pinning, and CRCI, with little changes between 12 and 24 months [43]. Thorninger et al also found that VLPF does not superiorly improve the functional outcomes after 5 weeks, 6 months, and 12 months compared to casting, and complication rates are similar [44]. However, modified K-wire fixation might be a safe, effective, rapid, and minimally invasive surgical option owing to higher patient satisfaction, shorter operation time, and a lower complication rate compared to ORIF [45].…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…As to unstable DRFs, in an RCT by the Wrist and Radius Injury Surgical Trial (WRIST) Group, the authors found no clinically meaningful PRO difference 24 months after injury across VLPF, external fixation (EF), percutaneous pinning, and CRCI, with little changes between 12 and 24 months [43]. Thorninger et al also found that VLPF does not superiorly improve the functional outcomes after 5 weeks, 6 months, and 12 months compared to casting, and complication rates are similar [44]. However, modified K-wire fixation might be a safe, effective, rapid, and minimally invasive surgical option owing to higher patient satisfaction, shorter operation time, and a lower complication rate compared to ORIF [45].…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Todos los artículos incluyeron intervenciones quirúrgicas tras una fractura de miembro superior, las fracturas se dan en mayor incidencia en mujeres que sufrieron la lesión debido a una caída (57,58), El uso del cuestionario DASH se utilizó para evaluar el nivel de funcionalidad antes de la lesión y después de la misma, para lo cual se realizó un seguimiento comprendido entre seis meses y doce meses en el que se mostraron mejores puntuaciones en la funcionalidad del paciente. A los 12 meses, la puntuación DASH fue 17,2 y 20, la diferencia clínicamente relevante mínima se definió como una diferencia de 16 a 20 puntos en DASH(53, 59, 60).…”
Section: Fractura De Miembro Superiorunclassified